Zebrafish-based assessment of luteolin’s potential in modulating seizure responses - Schneider, Sabrina Ester; Pedroso, Jefferson; Lima-Rezende, Cássia Alves; Mazon, Samara Cristina; dos Santos, Aline E.; Aguiar, Gean Pablo S.; Lanza, Marcelo; Hort, Mariana Appel; Oliveira, J. Vladimir; Piato, Angelo; Müller, Liz Girardi; Siebel, Anna Maria (Frontiers in Pharmacology, 2025)
IntroductionEpilepsy is a chronic neurological disorder marked by recurrent seizures. Neuroinflammation and mammalian target of rapamycin (mTOR) signaling are involved in neuronal hyperexcitability, contributing to the onset and persistence of seizures. Repeated seizures during development may cause cellular, cognitive, and behavioral impairment. About 30% of patients do not respond to available treatments, which emphasizes the need for new therapeutic options. Luteolin, a natural compound known for its anti-inflammatory properties and that modulates mTOR, is a promising candidate for seizure control. This study evaluated the antiseizure potential of luteolin and micronized luteolin in zebrafish (Danio rerio) larvae exposed to pentylenetetrazole (PTZ).Materials and MethodsFive-day-old zebrafish larvae were treated with embryo medium (control), diazepam (positive control), luteolin, or micronized luteolin, followed by PTZ exposure. Seizure frequency and intensity were recorded, along with occurrence and latency to seizure stages. Locomotor and behavioral responses were analyzed 24 h later. Brain tissue was used to assess molecular markers of inflammation (IL-1β, IL-6, TNF-α), mTOR signaling (p70S6Ka, p70S6Kb), and cell condition (BDNF, caspase-3).ResultsBoth luteolin presentations significantly reduced seizure incidence and severity. No locomotor or behavioral changes were observed 24 h after seizures when comparing PTZ-exposed animals to sham groups. Furthermore, molecular analyses revealed no significant changes in the expression levels of the tested markers 24 h after seizures.DiscussionThese findings provide initial evidence that luteolin, in both raw and micronized forms, has antiseizure properties in developing zebrafish. Further research is needed to uncover the pharmacokinetic profile and mechanisms involved.